(untitled) (Research, Society and Development, 2021)
Objective: The aim was to relate the experience of implementing the nursing interventional protocol for pediatrics patients with body temperature greater than 37,8 °C (100,04 °F). Methodology: This study is descriptive, exploratory, with a qualitative approach in an experience report of a medical students group and three nurses about the implementation of a clinical protocol, between the years 2019 and 2020. Results: In this protocol, it was decided to use the axillary measurement of temperature, with the fever being classified as greater than 37,8 °C (100,04 °F), contraindicating antipyretics if it was used less than 6 hours and/or drug allergies were reported. In infants older than three months, dipyrone and paracetamol were prioritized, in infants older than six months there is the possibility of ibuprofen usage. It was observed a resistance in parents and guardians in the beginning of the protocol application, meanwhile the clinical staff acceptance was immediate. The positive reflexes of teamwork and competent proactivity were observed by the academics regarding the service provided to the population. Conclusion: The implementation of protocols seeks to formalize work partnerships, acting as an instrument for standardizing the conduct and management of patients. The adoption of this measure brought benefits, providing a more organized, fast, humanized and quality service.